Strength and conditioning for grappling sports - Ratamess, N. A. (Strength and Conditioning Journal, 2011)
The grappling sports of judo, jiu-jitsu, and wrestling require the athlete to be in peak physical shape. Specific training targeting all health- and skill-related fitness conditioning components is needed to maximize success in grappling sports. Strength and condition programs for grapplers consist of weight, plyometric, agility, flexibility, speed, and aerobic training all properly periodized and integrated with sport practice to maximize performance at the appropriate time.